Psychosocial Factors in Patients Indicated for Lumbar Spinal Stenosis Surgery - Nechanicka, Nina; Barsa, Pavel; Harsa, Pavel (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
In the context of the interdisciplinary care of patients with chronic back pain, surgery is an option for those who do not benefit from conservative treatment. Psychological assessment prior to back surgery aims to identify suitable candidates for surgery and predict possible complications or poor treatment effects. The literature suggests that psychosocial factors are important outcome predictors of lumbar spinal surgery; however, there is not enough empirical evidence to show that early identification and treatment of these factors help improve surgical outcome. This review discusses the possible psychosocial risk factors in patients with lumbar spinal stenosis who are undergoing decompression or stabilization surgery, shows the association between presurgical psychological parameters and surgical treatment outcome, and describes the characteristics of our pilot study to implement presurgical psychological assessment in routine clinical practice.
Keywords: lumbar spinal stenosis; spinal surgery; psychosocial prognostic factors; outcome measures; review article